TUMBUH KEMBANG ANAK DAN POLA PENGASUHAN ORANG TUA PADA MASA GOLDEN AGE DI RA VINNAJA KABUPATEN MUARO JAMBI PROVINSI JAMBI - Nurul Annisa DN; Vivi Yumarni; Siti Marwah (Universitas Al-Hikmah Indonesia, 2021)
The purpose of this study was to determine whether the parenting styles applied by both parents had followed the predetermined methods, namely in the form of approach, habituation and service (the katsayan method). Parents and families are educational institutions that have a very big influence on children's development, therefore children's education cannot be separated from their families. Because the family is the first place where children claim to be social beings in interacting with their environment and groups. This activity is a form of community service, the STAI Ma'arif Jambi Early Childhood Islamic Education study program. The implementation of this research is in the form of PKM activities which are descriptive qualitative research. And this activity as a sabjek is the child of Raudathul Athfal VINNAJA, Kasang village, Karang City Rt, 03, Kumpeh Ulu sub-district, Muaro Jambi district, teachers and parents around the school. The results of this study were taken from a drawing competition using a cutton bath (as a brush) to draw and accompanied by parents. And seminars for parents (guardians of students) as an enrichment of knowledge for parents in RA vinnaja, while Islamic parenting was held with the theme